(untitled) (Comprehensive Journal of Science, 2025)
The significance of this research lies in several aspects, given the strategic importance of educational institutions in supporting sustainable development and improving the quality of life in cities. This topic is of particular importance in the municipality of Souk Al-Jum’ah, where education forms the cornerstone of human capacity-building and the promotion of social cohesion. The core of its importance lies in accurately identifying the gaps and shortcomings in educational buildings in terms of their number, geographical distribution, facilities, and compliance with locally and internationally approved planning standards. The research also contributes to the creation of a reliable database that can be relied upon for future planning and the development of educational infrastructure. By identifying problems and proposing solutions, the research aims to improve the educational environment in the municipality, ensuring that all age groups have access to high-quality education, which will have a positive impact on academic achievement, mental health, and the general well-being of the community.